Harnessing Daily Routines for Early Detection of Cool Executive Delays: Validating the EFORTS Questionnaire - Carmit Frisch; Sara Rosenblum (Children, 2024)
Bakground: The early identification of executive function (EF) delays should involve parental reports on children’s executive control in daily activities, capturing both “hot” and “cool” executive functions. This study aimed to revalidate the reliability and validity of the Executive Functions and Occupational Routines Scale (EFORTS) and examine whether it represents both hot and cool EFs Methods: Parents of 971 children (469 boys) aged 3 to 11 years (M = 6.08, SD = 1.8) completed the EFORTS and the Behavior Rating Inventory of Executive Functions/Preschool version (BRIEF/P). Exploratory and confirmatory factor analysis led to re–reestablishing the EFORTS daily functional routines with high internal consistency values (0.82–0.93). Results: Significant correlations were revealed between the EFORTS daily function subscales and various BRIEF/P “hot” and “cool” executive scales. Again, divided into three executive subscales, the EFORTS items showed medium-high internal reliability (α = 0.79–0.93). Significant age-related differences were demonstrated in the children’s EFs in three age groups: 3.0–5.11, 6.0–7.11, 8.0–11.11. Conclusions: The results suggest that EFORTS effectively assesses children’s executive control over daily functions, capturing both “cool” and “hot” EFs, making it a reliable tool for early detection of executive delays prior to formal schooling.